Gestão dos Riscos Urbanos em São Paulo: as áreas contaminadas - Jane Zilda dos Santos Ramires; Wagner Costa Ribeiro (Confins)
This paper presents the problems related to contaminated areas. This environmental issue was made public from the 1980s, through the process of industrial deconcentration verified in the denser urban areas of Brazil. In the first part it will be analyzed how this phenomenon, plus the change in urban land use, resulted in the emergence of risk areas, once the contaminated areas are being used or given new uses, such as residential or services, without having specific environmental studies with subsequent recovery and / or remediation.In order to help with the understanding, the scope and magnitude of this issue, it will be presented a mapping of the district, the existing industries in the urban area of São Paulo, which expresses the distribution of risks and dangers built up over decades in the municipality of São Paulo. In the second part, it will be discussed how the government handles this issue, their difficulties and achievements. Finally, the conclusions, which indicate that the effective implementation of legislation for the management of contaminated areas, the requirement of the completion of environmental studies, the availability of this information to the society, the increasing visibility of the problem, might lead to the solution of it, because even today, popular participation, incipient in this case, is vital to this process.